INNOVATION IN THE ISLAMIC RELIGIOUS EDUCATION CURRICULUM: A CASE STUDY OF NURURRAHMAN INTEGRATED ISLAMIC SENIOR HIGH SCHOOL - Usmayanti Nur Haliza; Bahrissalim Bahrissalim; Abdul Ghofur (Jurnal Konseling Pendidikan Islam, 2026)
This study aims to describe the innovation of the Islamic Religious Education (PAI) curriculum at SMAIT Nururrahman, particularly in the aspects of curriculum design, instructional implementation, religious habituation, and the supporting and inhibiting factors that influence its enactment. This qualitative case study involved PAI teachers, the vice principal for curriculum affairs, and students as key informants. Data were collected through observation, interviews, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldana. The findings show that SMAIT Nururrahman integrates the Independent Curriculum with an Islamic-based curriculum emphasizing worship habituation, tahfiz programs, and character centered learning. Innovations are reflected in various learning methods such as discussion, case studies, PBL, PJBL, and the use of digital technology through LMS and interactive media. Religious habituation such as daily Qur’an recitation, congregational prayers, MABIT, and dauroh effectively contributes to students’ spiritual development. Supporting factors include teacher commitment, adequate facilities, and school policies, while challenges arise from limited technological mastery among some teachers and classroom management issues during certain learning hours. Overall, the innovation of the PAI curriculum at SMAIT Nururrahman positively impacts students’ discipline, learning motivation, and religious character.